WAYS TO INCREASE EXPORT OF FRUITS AND VEGETABLES IN THE REGION - Fayzieva Shirin, Shodmonovnaa (THE INNOVATION ECONOMY, 2025)
This article explains the regulatory framework for the production and export of fruits and vegetables in the economy of Uzbekistan, and also substantiates the directions for development of the industry in the future